왁스플라워 ‘Mars’와 ‘Early Nir’ 반숙지 삽목발근에 미치는 K-IBA 엽면시용 효과 - 정현환(Hyun Hwan Jung); 김세진(Se Jin Kim); 양경록(Gyeong-Rok Yang); 이영란(Young-Ran Lee) (Weon'ye gwahag gi'sulji, 2023)
본 연구는 왁스플라워 삽목시 K-IBA 완전침지와 삽목 후 엽면살포처리로 발근율과 묘소질을 향상시킬 목적으로 수행하였다. 완전침지는 삽수 전체를 K-IBA 500, 1,000, 2,000, 4,000mg·L-1 용액에 30초, 1, 2, 4분간 담근 후 삽목하였고, 엽면살포는삽목 후 동일한 농도의 용액을 1주간격으로 1, 2, 4, 8주간 약액이 엽면에서 흘러내릴 정도로 살포하였다. 왁스플라워 ‘Mars’는 5월 삽목시 K-IBA 2,000, 4,000mg·L-1 용액에 2분간 완전침지 후 삽목하였을 때 발근율이 40% 이상까지 높아졌으며, 9월삽목에서는 K-IBA 500, 1,000mg·L-1 용액을 엽면살포하였을 때 발근율이 50% 이상까지 증가하였다. ‘Early Nir’는 10월 삽목시 완전침지 처리는 K-IBA농도가 증가할수록 생존율과 발근율을 향상시켰으며, 농도와 처리시간 증가에 따른 역효과는 나타나지 않았다. K-IBA 2,000, 4,000mg·L-1 용액에 2, 4분간 침지하면 발근율이 50% 이상으로 향상되었으며, 엽면살포 처리도 생존율과 발근율을 대조구에 비해 향상시켰으나 최대 발근율은 40% 이하로 낮았으며 살포횟수가 증가할 수록 효과는 감소하였다. 위의 결과로부터 생존율, 발근율, 묘소질을 종합적으로 고려할 때 ‘Mars’는 9월 삽목 시 K-IBA 500, 1,000mg·L-1 용액을 엽면살포하고, ‘Early Nir’는 10월 삽목시 삽수를 4,000mg·L-1 용액에 2, 4분간 완전침지하는 것이 삽목 증식효율을 각각 높일 수 있을 것으로 판단되었다. This study was carried out to improve the rooting percentage and rootstock quality of Chamelaucium uncinatum ‘Mars’ and ‘Early Nir’ semi-hardwood cuttings with K-IBA total immersion or as a foliar spray application. In the total immersion case, all cuttings were immersed in K-IBA 500, 1,000, 2,000, and 4,000 mg·L-1 solutions for 30 seconds or for 1–4 minutes, after which they were stuck into the media. The foliar spray was applied with a solution at the same concentration to the extent that the solution dripped down from the leaf surface at one-week intervals over one, two, four, or eight weeks after cutting. Total immersion with the K-IBA 2,000 and 4,000 mg·L-1 solutions for two minutes increased the rooting ratio by more than 40% for waxflower ‘Mars’ cuttings in May. The K-IBA 500 and 1,000 mg·L-1 foliar spray applications also increased the rooting percentage by more than 50% for cuttings in Septembers. With regard to ‘Early Nir’ cutting propagation in October, the survival ratio and rooting percentage increased when immersed in the K-IBA solution, showing no adverse effects even with increasing the concentration and immersion time. The rooting percentage exceeded 50% when immersed for two and four minutes at 4,000 mg·L-1. The K-IBA foliar application also improved the survival percentage and rooting ratio, but the rooting percentage was less than 40% and decreased as the spray time was increased. From the above results, foliar spray drip down with K-IBA 500 and 1,000 mg·L-1 solutions for ‘Mars’ in September and total immersion in the K-IBA 4,000 mg·L-1 solution for two or four minutes with ‘Early Nir’ in October can be used to increase the cutting propagation efficiency of semi-hardwood cuttings, respectively. KCI Citation Count: 1